Thiết kế và cài đặt hệ nén dữ liệu thông minh IDCS - Thủy, Nguyễn Thanh (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall investigate some features of the system IDCS (Intelligent Data Compressing System) which based on the nature and characteristics of a data file f and using a library of compressing routine L, could choose the most convenient compressing program C ÎL, by inferring over a knowledge base K in the form of rules. It is interesting that the more complete the knowledge base K, the more effective the chosen compressing C.